The components of predation in Culpeo Foxes (Lycalopex culpaeus), and the value of long-term observations - Kelt, Douglas A. (2025)
Understanding predator-prey dynamics requires insight on predator responses to variation in prey abundance. Whereas most predators respond numerically to changes in food availability, functional responses are less clear. Characterizing both is essential to understanding how predator-prey dynamics will change with spatiotemporal variation in resources or habitat conditions. The Culpeo (Lycalopex culpaeus) is a wide-ranging South American canid broadly characterized as a generalist forager exhibiting numerical responses, but limited functional responses, to variation in prey availability. We employ a 23-year perspective on the diet of Culpeos, using monthly demographic monitoring of small mammal prey species and concurrent collection of Culpeo scat in a large protected area in Chile. As elsewhere, Culpeos emphasize small mammals in their diet, but they consistently consume some species (notably Abrocoma bennettii) disproportionate to their apparent availability. Culpeos here display limited numerical responses to variation in small mammal abundance, although this weakens during ex-tended periods of low small mammal availability when foxes presumably switch to other food items. Culpeos exhibit an asymptotic (Type II) functional response to variation in abundance of small mammal prey. While Type II functional responses are generally considered to charac-terize specialist predators, these patterns match expectations for a generalist forager that strongly favors certain prey species, and underscore the importance of long-term data for elucidating fundamental ecological patterns. Further work is needed to dissect this functional response among key prey species, and to determine if and how this may fluctuate with climatic conditions, which vary extensively here due to El Niño Southern Oscillations. Long-term datasets provide unique opportunities to understand and characterize such patterns in natural communities.